(untitled) (Economic and Political Thought, 2016)
German geopolitics is burdened with “original sin” – when in the years 1933–1945 it was used for the policy of conquests, it justified mass war crimes committed by the Third Reich. That is why after World War II the main assumptions of German geopolitics were discredited and discontinued. Contemporary discussion on German geopolitics is mainly based on the consequences of the central location of Germany in Europe. Elements of geopolitics can be found in the role of Germany as an intermediary between Russia and the West, special treatment of Russia and solving the migration crisis. It revealed new divisions between Eastern Europe and Western Europe, which refer to the old visions of geopolitical interests of national states.